Simulación del Acoplamiento Dinámico en Sistemas Represa-Embalse Utilizando Elementos Finitos Acústicos (Journal on studies and research of academic knowledge, 2018)
Acoustic finite elements are used to simulate the propagation of hydrodinamic waves within the reservoir of a dam during a dinamic event. To study their feasibility, 3 study cases were taken: the main section of the Itaipú dam (gravity dam), Lumiei (arch dam) and Pertusillo (arch-gravity dam). After being validated with known problems from literature, the method was applied to the study cases, removing theconstrictive contour conditions an assessing their effects. Viscous damping turned out to be necessary to avoid acoustic beating phenomenom. Energy apsortion from the sediments in the bottom of the reservoir is important and should be considered. Water level modifies the period of the coupled system and high frecuencies amplification.Vertical vibrations have negligible effects in curved dams. Water compressibility and dam flexibility are the most important factors, as they allow the full couplement and dynamicamplification, respectively. The proposed method agrees with solutions  commonly adopted in professional practice, within the range where they are valid, improving the precision outside of it, with a reasonable computational cost.
Keywords: Dams; dynamic coupling; acoustics; contour conditions; amplification